Structural systematics of aryl-1,3-dithiane derivatives: crystal and energy-minimised structures, and Hirshfeld surface analysis - Zukerman-Schpector, Julio; Sousa Madureira, Lucas; Stefani, Hélio A.; Gozhina, Olga; Tiekink, Edward R. T. * (De Gruyter, 2016)
The crystal structure analysis of three aryl-1,3-dithiane derivatives, with aryl=4-methylphenyl (1), 4-chlorophenyl (2) and 2,4-dichlorophenyl (3), shows the three molecules to have very similar conformations, with the aryl ring lying on an approximate mirror plane that bisects the dithiane ring which adopts a chair conformation; the energy-minimised structures are consistent with the experimental structures. The greater barrier to rotation about the methine-C–C(ipso) bond in 3, cf. 1 and 2, is related to unfavourable intramolecular S···Cl interactions in the putative transition state. The molecular packing in 1–3, while globally similar, are distinct, being based on combinations of identifiable C–H···π(arene), C–H···S and C–Cl···π(arene) interactions. The lack of isostructural relationships points to the significance of the identified intermolecular interactions to direct molecular packing.